Mujeres campesinas :
Contains a short documentary in 4 different languages (spanish, english, french and portuguese) DVD realized on the occasion of the 4th Women's Assembly, in connection with the 6th International Conference of La Via Campesina (Jakarta, Indonesia, June 2013)